DUALISME DESA DI BALI : SINERGITAS PENGELOLAAN KEPARIWISATAAN BUDAYA BALI - A.A. Istri Eka Krisna Yanti; Anak Agung Istri Ari Atu Dewi; A.A. Ngurah Oka Yudistira Darmadi; I Gede Pasek Pramana; Putu Devi Yustisia Utami (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study examines the dualism of village governance in Bali, reflected in the coexistence of Desa Dinas (administrative villages) and Desa Adat (customary villages), and its implications for the administration of cultural tourism. This dualism is a historical and juridical consequence of two systems of authority operating simultaneously within the same social space: the administrative governmental system and the customary legal system. In practice, the overlap of authority and territorial boundaries between these two village institutions often leads to disharmony, particularly in the management of tourist attractions and the imposition of tourism levies. This study employs a normative legal research method using statutory and conceptual approaches through an examination of relevant legislation and conceptual frameworks governing tourism administration at the village level. The findings reveal that the ideal administration of Bali’s cultural tourism requires institutional synergy between Desa Dinas, Desa Adat, and the Regional Government, especially in the determination and collection of tourism levies, which legally may only be established through regional regulations. Harmonizing authorities, strengthening technical regulatory frameworks, and developing operational cooperation mechanisms are urgent necessities to prevent authority conflicts and to ensure accountable, sustainable, and community-oriented tourism governance. This study underscores that cultural tourism management can only operate optimally when village dualism is placed within a coordinated and integrated framework aligned with the regional governance system.